Design of a Hemispherical Reconfigurable Frequency Selective Surface Using Water Channels - Son, Dong Chan; Shin, Hokeun; Kim, Yoon Jae; Hong, Ic Pyo; Chun, Heoung Jae; Jung, Kyung Young; Choo, Hosung; Park, Yong Bae (IEEE Access, 2018)
In this paper, we propose a hemispherical reconfigurable frequency selective surface (FSS) using water channels. The switching between band-pass and band-stop states is possible since the water with a high dielectric constant can control the effective permittivity of the structure. We simulate and fabricate the FSS and measure the radiation pattern of FSS enclosed horn antenna to check the reconfigurable characteristic of the hemispherical FSS. The simulated results show a good agreement with the measured results.
Keywords: Effective permittivity; High dielectric constants; Measured results; Reconfigurable characteristic; Reconfigurable frequency selective surfaces; Simulated results; Slabs; Water channels; Frequency selective surface; hemisphere radomes; water channels